An Arctic Intertidal Population of Macoma balthica (Mollusca, Pelecypoda): Genotypic and Phenotypic Components of Population Structure - Green, Roger H.; Singh, Shiva M.; Hicks, Beverly; McCuaig, Janet M. (Canadian Journal of Fisheries and Aquatic Sciences, 1983)
In July 1980 we collected live Macoma balthica from populations at two tide levels near Fort Churchill, Man., Canada. Upper lethal temperature tolerances were determined for clams from the mean low water (MLW) tidal level and from 1.1 m above MLW tidal level, after which all specimens were hard frozen for later electrophoretic analysis. Of 22 loci evaluated, the following were polymorphic: AKP, ACP, EST, LAP, MDH, and ME. Genotypes at these loci were related to tide level, growth rate, tolerance to high temperature, and age. Analysis of shell annual rings verified an earlier report of much faster growth in the higher tide level population. Growth rate and degree of heterozygosity are both higher at 1.1 m than at MLW. Degree of heterozygosity increases with age, suggesting selection against homozygotes. At 1.1 m, but not at MLW, individuals with higher growth rates have lower tolerance to high temperatures and a higher degree of heterozygosity. Similar patterns are described for the six individual loci.